The BRICS on climate change global governance - Rinaldi, Augusto Leal (2017)
This article aims at assessing the evolution of BRICS’ positions on climate change global governance. We discuss the implications of that positioning for the role of the group on that theme. From the analysis of the main regimes and agreements, we argue that although there is a disposition to act in multilateral forums, they face a series of constraints that makes difficult for them to adopt a common ground.